Tyrosinase-based production of L-DOPA by Corynebacterium glutamicum - SARIYAR AKBULUT, BERNA (SPRINGER, 2021)
An increase in the number of elderly people suffering from the symptoms of Parkinson's disease is leading to an expansion in the market size of 3,4-dihydroxyphenyl-l-alanine (l-DOPA), which is the most commonly used drug for the treatment of this disease. Need for better quality products through economically feasible and sustainable processes makes biotechnological approaches attractive. The current study is focused on heterologous expression of Ralstonia solanacearum tyrosinase in Corynebacterium glutamicum cells to produce l-DOPA during growth on glucose or glucose/xylose mixtures. Whole-cells pre-grown on glucose were further exploited for biotransformation of l-tyrosine to l-DOPA. To prevent l-DOPA oxidation, not only the most commonly used agent, ascorbic acid, but also for the first time, thymol was evaluated. The highest l-DOPA titer was 0.26 +/- 0.02 g/L at the end of growth on a mixture of 1% xylose and 3% glucose in the presence of 200 mu M thymol as the oxidation inhibitor. The ability to co-utilize glucose and xylose to reach this titer could make these cells ideal for l-DOPA production using hydrolyzed lignocellulosic biomass. When the pre-grown cells were further used for biotransformation, the highest l-DOPA yield was 0.61 +/- 0.02 g/gDCW with 4 mM ascorbic acid. Since l-tyrosine biotransformation is primarily dependent on tyrosinase activity, yield in this route could be improved by optimizing reaction conditions. As the industrial workhorse for amino acid production, these C. glutamicum cells will clearly benefit from strain development efforts and bioprocess optimization towards sustainable and economically feasible l-DOPA production.
Keywords: Corynebacterium glutamicum; L-DOPA; Tyrosinase; Ascorbic acid; Thymol; ESCHERICHIA-COLI; BIOTECHNOLOGICAL PRODUCTION; ASCORBIC-ACID; 3,4-DIHYDROXYPHENYL-L-ALANINE; INHIBITORS; HISTIDINE; GLUTAMATE; THYMOL; STRAIN; MUTANT